Verg. Ecl. 9, 44-55: singers, songs, fiction of orality (Argos, 2022)
Regarding Verg. Ecl. 9, 44-55 the manuscript tradition is not uniform: most of the MSS assign vv. 46-50 to Meris; a few (M and γ) assign them to Lycidas. The article provides substantiation for the attribution of these verses to Lycidas; it reviews various solutions adopted in recent editions and commentaries, including the latest critical edition (Ottaviano., 2013), which (wrongly in our view) adopts the emendation nisi in v. 45. The four evocations of song made by Lycidas and Meris are then analysed within the framework of two timely points made by Schmidt (1972): a. the particular concept of ‘authorship’ that governs the fiction of orality proper to bucolic poetry; b. the relationship established in the eclogue between the content of these evocations and the categories of poeta and uates stated in vv. 32-36.
Keywords: Vergil; Eclogue 9; Bucolic poetry; Poeta; Vates